Geotechnical Characteristics of Volcanic Red Clay Soil Related to Geoengineering Problem in Sekincau, Sumatra, Indonesia - et al., Prahara Iqbal (International Journal of Advanced Science and Technology, 2020)
The study of physical, mechanical, and mineralogy characterization of volcanic red clay soil in the Sekincau Sub-District, West Lampung, Indonesia to obtain the genetic and soil engineering characterization related to the geoengineering problem. The method of this study is the Geotechnical laboratory method, XRD, and SEM method. The results of the analysis show that the volcanic red clay soil in the study area is residual soil produced from the weathering of volcanic rocks composed of felsic minerals in tropical environments. This soil is clayey silt (MH), loose, easily eroded, has the specific gravity 2.52 - 2.90, water content 27.21% - 67.14%, water saturation 72.98% - 94.75%, porosity 54.43% - 67.00%, the liquid limit value of 52.54- 121.17%, a plasticity index value of 17.82-35.17%, permeability 7.4E-08 - 7.22E-05, has cohesion less than 1 Mpa, and an internal friction less than < 30o. Quartz, halloysite, kaolinite, and montmorillonite are the clay minerals that can be found in this soil. It can be concluded that volcanic red clay soil in the study area is easy to landslide during the rainy season.